Isoliquiritigenin is a potent inhibitor of NLRP3 inflammasome activation and diet‐induced adipose tissue inflammation. Issue 6 (10th September 2014) - Honda, Hiroe; Nagai, Yoshinori; Matsunaga, Takayuki; Okamoto, Naoki; Watanabe, Yasuharu; Tsuneyama, Koichi; Hayashi, Hiroaki; Fujii, Isao; Ikutani, Masashi; Hirai, Yoshikatsu; Muraguchi, Atsushi; Takatsu, Kiyoshi
Abstract : Isoliquiritigenin, a component of Glycyrrhiza uralensis, is a potent inhibitor of the NLRP3 inflammasome, and suppresses diet‐induced obesity, adipose tissue inflammation, and metabolic disorders. Abstract : Inflammasome activation initiates the development of many inflammatory diseases, including obesity and type 2 diabetes. Therefore, agents that target discrete activation steps could represent very important drugs. We reported previously that ILG, a chalcone from Glycyrrhiza uralensis, inhibits LPS‐induced NF‐κB activation. Here, we show that ILG potently inhibits the activation of NLRP3 inflammasome, and the effect is independent of its inhibitory potency on TLR4. The inhibitory effect of ILG was stronger than that of parthenolide, a known inhibitor of the NLRP3 inflammasome. GL, a triterpenoid from G. uralensis, had similar inhibitory effects on NLRP3 activity, but high concentrations of GL were required. In contrast, activation of the AIM2 inflammasome was inhibited by GL but not by ILG. Moreover, GL inhibited NLRP3‐ and AIM2‐activated ASC oligomerization, whereas ILG inhibited NLRP3‐activated ASC oligomerization. Low concentrations of ILG were highly effective in IAPP‐induced IL‐1β production compared with the sulfonylurea drug glyburide. In vivo analyses revealed that ILG potently attenuated HFD‐induced obesity, hypercholesterolemia, and insulin resistance. Furthermore, ILG treatment improved HFD‐induced macrovesicular steatosis in the liver. Finally, ILG markedly inhibited diet‐induced adipose tissue inflammation and IL‐1β and caspase‐1 production in white adipose tissue in ex vivo culture. These results suggest that ILG is a potential drug target for treatment of NLRP3 inflammasome‐associated inflammatory diseases.